Flame retardancy and thermal properties of rigid polyurethane foam conjugated with a phosphorus–nitrogen halogen-free intumescent flame retardant. (May 2020) - Lin, Zhaojun; Zhao, Qianqiong; Fan, Ruilan; Yuan, Xiaoxue; Tian, Fuli
In this work, a halogen-free intumescent combining phosphorus and nitrogen, flame-retardant 2-((2-hydroxyphenyl)(phenylamino)methyl5, 5-dimethyl-1, 3, 2-dioxaphosphinane 2-oxide (HAPO) was successfully synthesized. It had been synthesized by reaction of 5, 5-dimethyl-1, 3, 2-dioxphosphinane 2-oxide with Schiff base. Its chemical structure was characterized in detail by Fourier transform infrared spectroscopy, 1 H NMR, and 31 P NMR spectrum. The flame-retardant polyurethanes were prepared with different loadings of HAPO. The thermal properties, flame retardancy and combustion behavior of the pure polyurethane foam thermosets were investigated by a series of measurements involving thermogravimetric analysis, limited oxygen index measurement, UL-94 vertical burning test, and cone calorimeter test. The results of the aforementioned tests indicated that HAPO can significantly improve the flame retardancy as well as smoke inhibition performance of polyurethane foam. Compared with the PU-Neat, the limited oxygen index of flame-retardant polyurethanes (15%) thermoset was increased from 19.5% to 23.8% and its UL-94 reached V-0 rating. In addition, the cone test results showed that the heat release rate, total heat release, rate of smoke release, and total smoke production of flame-retardant polyurethanes (10%) were decreased obvious sly. The apparent morphology of carbon residue was characterized by scanning electron microscopy, and results revealed that the modified polyurethane foam can form dense carbon layer after combustion. Thermogravimetric analysis results also indicated that the char amount of flame-retardant polyurethanes was obviously increased compared with PU-Neat. Based on the above analysis, we can draw the conclusions which in the condensed phase, phosphorus-based acids from the degradation of HAPO, this could promote the formation of continuous and dense phosphorus-rich carbon layer. In the gas phase, the flame-retardant mechanism was ascribed to the quenching effect of phosphorus-based radicals and diluting effect by non-flammable gases.